Pelatihan Produksi Video Bagi IPNU IPPNU Untuk Penguatan Dakwah Digital - Arifudin, Dani; Gunawan Pamuji; Bhakti Sihanjono (PT. Karya Inovatif Nusantara, 2025)
Digital transformation has brought significant changes across various aspects of life, including the dissemination of information and religious practices. In the context of mosques, high-quality audiovisual documentation has become an effective strategy to enhance the visibility and role of mosques as centers of religious, social, and educational activities. However, observations of IPNU and IPPNU youth in Banyumas Regency indicate that there are still challenges in utilizing this technology, particularly in producing high-quality mosque profile videos. The main obstacles include a lack of technical skills in video production, limited access to production equipment, and a lack of understanding of effective digital content strategies. As a solution to these issues, the Mosque Profile Video Production Training Program was designed to equip mosque youth with video production skills, including cinematography techniques, scriptwriting, editing, and digital publishing strategies. In addition, this program also aims to help participants optimize the use of mosque social media as a more engaging platform for da’wah and public outreach. This training is intended to improve the quality of mosque audiovisual documentation, encourage innovation in digital da’wah, and strengthen youth involvement in utilizing technology as a broader and more effective means of Islamic propagation.